2015
DOI: 10.1186/s13063-015-1054-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acupuncture and computer-assisted cognitive training for post-stroke attention deficits: study protocol for a randomized controlled trial

Abstract: BackgroundA majority of stroke survivors present with cognitive impairments. Attention disturbance, which leads to impaired concentration and overall reduced cognitive functions, is strongly associated with stroke. The clinical efficacy of acupuncture with Baihui (GV20) and Shenting (GV24) as well as computer-assisted cognitive training in stroke and post-stroke cognitive impairment have both been demonstrated in previous studies. To date, no systematic comparison of these exists and the potential beneficial e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Although most of the previous studies on acupuncture treatment of cognitive impairment used a combination of body acupuncture points and head acupoints [23][24][25], we will use only two acupuncture points on the head (GV20 and GV24) for treatment, which is based on the results of literature analysis and a continuation of previous research [26,27]. On the other hand, uni ed acupuncture points may reduce variables and increase the accuracy and persuasion of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Although most of the previous studies on acupuncture treatment of cognitive impairment used a combination of body acupuncture points and head acupoints [23][24][25], we will use only two acupuncture points on the head (GV20 and GV24) for treatment, which is based on the results of literature analysis and a continuation of previous research [26,27]. On the other hand, uni ed acupuncture points may reduce variables and increase the accuracy and persuasion of this study.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of Shenting (DU24) is similar to Baihui. These two acupoints are often used in combination in clinical practice [ 12 ]. In modern times, many studies using animal models of stroke have revealed that acupuncture at the Baihui (DU20) and Shenting (DU24) acupoints can ameliorate the learning and memory deficits of rats with cerebral ischemia/reperfusion (I/R) injury [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The EA device (Hwato, SDZ-III, Suzhou, China) is placed behind the patient to ensure that the patient does not know the specific frequency parameters of the intervention. Patients should receive an intervention last for 4 weeks (30 min a day, 5 days a week, Monday to Friday) [ 12 ]. During the intervention, patients are asked to be quiet to minimize other interference factors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Acupuncture, as an important part of the appropriate technology of traditional Chinese medicine (TCM), is currently the most commonly used complementary and alternative treatment [8].. Acupuncture has a significant regulating effect on human psychology. Modern studies have found that acupuncture can improve cognitive function by affecting cerebral blood flow and hemorheology, protecting the internal structure of brain nerve cells [9].…”
Section: Introductionmentioning
confidence: 99%